2006
DOI: 10.1073/pnas.0507683103
|View full text |Cite
|
Sign up to set email alerts
|

Sleeping Beauty transposase modulates cell-cycle progression through interaction with Miz-1

Abstract: We used the Sleeping Beauty (SB) transposable element as a tool to probe transposon-host cell interactions in vertebrates. The Miz-1 transcription factor was identified as an interactor of the SB transposase in a yeast two-hybrid screen. Through its association with Miz-1, the SB transposase down-regulates cyclin D1 expression in human cells, as evidenced by differential gene expression analysis using microarray hybridization. Down-regulation of cyclin D1 results in a prolonged G 1 phase of the cell cycle and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 33 publications
0
39
0
Order By: Relevance
“…The chromatin binding protein HMGB1 was identified as a host cofactor for the SB transposase and was shown to increase transposition in mammalian cell lines (Zayed et al, 2003). In addition, the transcription factor Miz-1 was shown to interact with the SB transposase (Walisko et al, 2006). These, and potentially other host factors, may influence the efficiency of SB transposition and should be considered when using SB in different cells and organisms.…”
Section: Introductionmentioning
confidence: 99%
“…The chromatin binding protein HMGB1 was identified as a host cofactor for the SB transposase and was shown to increase transposition in mammalian cell lines (Zayed et al, 2003). In addition, the transcription factor Miz-1 was shown to interact with the SB transposase (Walisko et al, 2006). These, and potentially other host factors, may influence the efficiency of SB transposition and should be considered when using SB in different cells and organisms.…”
Section: Introductionmentioning
confidence: 99%
“…2). We have shown that downregulation of cyclin D1 by the SB transposase is associated with a decrease of cyclin D1/cdk4-specific phosphorylation of Rb, thereby potentiating a delay in the G 1 /S transition 25 (Fig. 2).…”
Section: Cell Cycle Regulation By the Sleeping Beauty Transposasementioning
confidence: 99%
“…In a combined approach of genome-wide expression analysis by gene chip hybridization and yeast two-hybrid cloning, we found that the SB transposase downregulates expression of the cyclin D1 gene through physical interaction with the host-encoded Miz-1 protein 25 ( Fig. 2).…”
Section: Cell Cycle Regulation By the Sleeping Beauty Transposasementioning
confidence: 99%
See 1 more Smart Citation
“…There are a number of proteins described to interact with the SB transposase, most of which are involved in DNA repair processes or in cell cycle regulation (Zayed et al, 2003;Izsvák et al, 2004;Walisko et al, 2006). As these proteins could differ in their cell type-specific distribution and activity, we measured the mRNA expression levels of four SBinteracting factors (DNAPKcs, HMGB1, Ku70, Ku80) in the HeLa and HEK-293 cell lines.…”
Section: Comparing Transgenic Rates Of Various Transposon Systems In mentioning
confidence: 99%